2018
DOI: 10.1002/pc.24971
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of bamboo and flax fiber reinforced polylactic acid filaments for fused deposition modeling (FDM)

Abstract: A new type of fiber reinforced filament materials for Fused Deposition Modeling applications has been developed. Polylactic acid (PLA), compounded with two types of plasticizer, is reinforced with bamboo and flax fibers. The fiber fractions are characterized by measuring their length (l) over diameter (d) before and after compounding so that the effect of the l/d on the final filament properties can be systematically studied. The pre‐processing and processing activities, to produce filaments with a diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 28 publications
3
74
0
Order By: Relevance
“…Although there are quite a few studies on PLA-based biocomposites in FDM, the challenges brought by the material coupled to the ones coming from the processing method have forced a “trial and error” procedure. Interestingly, the available literature that does not make use of commercial filaments is significant [3,9,17,21,23,38,39,45,46,48,49,65,66,67,68], but has appeared only recently and the effects of processing parameters, additives formulation, patterning and geometrical features are not yet deeply explored. As can be seen from Table 3, plasticizers [21,45,48], toughening agents [39,65] and compatibilizers [39] have been studied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are quite a few studies on PLA-based biocomposites in FDM, the challenges brought by the material coupled to the ones coming from the processing method have forced a “trial and error” procedure. Interestingly, the available literature that does not make use of commercial filaments is significant [3,9,17,21,23,38,39,45,46,48,49,65,66,67,68], but has appeared only recently and the effects of processing parameters, additives formulation, patterning and geometrical features are not yet deeply explored. As can be seen from Table 3, plasticizers [21,45,48], toughening agents [39,65] and compatibilizers [39] have been studied.…”
Section: Methodsmentioning
confidence: 99%
“…Notice also that the negative effect of biofiller is independent of filler geometry. In fact, Depuydt [48] et al analyzed PLA filled with flax and bamboo fibers as a function of the length over diameter ratio (L/D) of the reinforcement. Despite their results showed that the L/D ratio had an important influence on stiffness (longer fibers increase it by 215%), it did not have the same influence on strength, and anyway the properties of neat PLA were much higher.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The abilities to fabricate complex geometries and lower cost of manufacturing have made research studies motivated into various characterizations and improvements of parts fabricated by FFF. [5][6][7] Despite the mentioned advantages, mechanical properties of parts manufactured by FFF process are inherently poor, [8] which is why it is required to consider the mechanical properties of 3D-printed materials compared with the conventional methods. [9] In order to have a better understanding of the features of temperature profile between adjacent filaments, various mathematical approaches have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“… ( a ) The maximum tensile strength with fiber wt.% [ 30 , 34 , 35 , 38 , 39 , 40 , 41 , 42 , 44 , 47 , 51 , 62 ]. ( b ) the maximum tensile strength with fiber wt.% [ 36 , 37 , 52 , 54 , 55 , 63 , 64 , 66 , 68 , 70 , 71 , 72 ]. …”
Section: Figurementioning
confidence: 99%